The high occurrence of multidrug-resistant Salmonella spp. isolated from raw chicken meat and contact surfaces at wet market in Malaysia - Asif Sukri; Siti Shahara Zulfakar; Illya Syahirah Mohd Taib; Nurul Fathiah Omar; Noraziah Mohamad Zin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Post-slaughter processing steps during poultry meat production contribute to Salmonella contamination and may transmit multidrug-resistant Salmonella to chicken meats and contact surfaces. This study was undertaken to identify Salmonella spp. strains isolated from chicken meats and their contact surfaces, and to determine their antibiotic resistance profiles. A total of 20 samples were collected from raw chicken meat and its contact surfaces from a shop in Pasar Chow Kit, Kuala Lumpur. Identification of presumptive Salmonella colonies was conducted by using biochemical tests and multiplex polymerase chain reaction (PCR). Antibiotic susceptibility test was conducted by using Kirby-Bauer disk diffusion method against 11 antibiotics. Salmonella enterica Group I was only detected in seven samples. The antibiogram testing showed that all the seven Salmonella isolates (100%) were multidrug-resistant and all isolates were resistant to penicillin, chloramphenicol, erythromycin, and tetracycline. Resistance towards trimethoprim-sulfamethoxazole, amoxicillin and ampicillin was observed in four isolates. However, sensitivity was recorded for cephalexin, cefoxitin, cefotaxime, and ceftriaxone in six isolates. The highest multiple antibiotic resistance (MAR) index of 1.00 (resistance to all eleven antibiotics tested) was observed in one isolate (P2) while the lowest MAR index of 0.36 (resistance to four antibiotics tested) was observed in three isolates (CB, M2 and M3). Our results demonstrated that raw chicken and meat contact surface were a source of multidrug-resistant Salmonella and can contribute to significant health concern in Malaysia. Stringent hygienic procedure during chicken meat processing should be therefore be practised.